Improving Writing Skills; An Implementation of “Think Pair Share” for Islamic Junior Schools Students - Suhrowardi Suhrowardi (Universitas Pendidikan Mandalika, 2020)
The objectives of this study are to capture the implementation of Think Pair Share (TPS) in teaching-learning process, to identify the improvement of the students' writing skills, and to find out the strengths and the weaknesses of Think Pair Share (TPS) in the teaching-learning process of the seventh-grade students of MTS AL Islahuddin Kediri. This research is a classroom action research. The researcher used qualitative and quantitative data. The qualitative data was interview and observation. The quantitative data was tested. The step to analyze the qualitative data used data reducing, data display, and conclusion drawing. The step to analyze the quantitative data used mean formula. The result of the research shows that there are positive improvements in either student